Triage considerations for patients referred for structural heart disease intervention during the COVID‐19 pandemic: An ACC/SCAI position statement. Issue 3 (8th June 2020) - Shah, Pinak B.; Welt, Frederick G. P.; Mahmud, Ehtisham; Phillips, Alistair; Kleiman, Neal S.; Young, Michael N.; Sherwood, Matthew; Batchelor, Wayne; Wang, Dee Dee; Davidson, Laura; Wyman, Janet; Kadavath, Sabeeda; et al.
Abstract: The coronavirus disease‐2019 (COVID‐19) pandemic has strained health care resources around the world, causing many institutions to curtail or stop elective procedures. This has resulted in an inability to care for patients with valvular and structural heart disease in a timely fashion, potentially placing these patients at increased risk for adverse cardiovascular complications, including CHF and death. The effective triage of these patients has become challenging in the current environment, as clinicians have had to weigh the risk of bringing susceptible patients into the hospital environment during the COVID‐19 pandemic against the risk of delaying a needed procedure. In this document, the authors suggest guidelines for how to triage patients in need of structural heart disease interventions and provide a framework for how to decide when it may be appropriate to proceed with intervention despite the ongoing pandemic. In particular, the authors address the triage of patients in need of transcatheter aortic valve replacement and percutaneous mitral valve repair. The authors also address procedural issues and considerations for the function of structural heart disease teams during the COVID‐19 pandemic.